The impact of external borrowing to bridge the federal budget deficit of the Republic of Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The deficit budget, one of the results of increased public spending for their revenues due to the economic pressures imposed by the interest of the economies of those countries from the need to increase government spending in order to revitalize the national economy and accelerate economic growth rates and provide employment to the growing levels of unemployment in those countries opportunities and what is required to address the current debt crisis (borrowing), which has become a big burden on the governments and the need to move towards the application of austerity spending and tax increases, which inevitably forced those countries will be reflected reduced spending on basic aspects of life and their peoples, particularly earners medium and enter the few and the poor such as the freezing of salaries and reduce the costs of education and social welfare and pension rights and the other with a direct impact on the welfare of the peoples of public expenditures.